Geospatial Analysis of the Proportion of Persons Defined as Underrepresented in Medicine for Each Medical School and Their Surrounding Core-Based Statistical Area - Zoel A. Qui??nez; Angel Benitez-Melo; Laura M. Diaz; Michael Lennig; Danton Char; Charlotte Smith (Mary Ann Liebert, 2024)
Background: The current approach to increasing diversity in medical education fails to consider local community demographics when determining medical school matriculation. Purpose: We propose that medical schools better reflect their surrounding community, both because racially/ethnically concordant physicians have been shown to provide better care and to repair the historical and current racist impacts of these institutions that have criminalized, displaced, and excluded local Black and Brown communities. Methods and Results: In this study, we used geospatial analysis to determine that medical school enrollments generally fail to reflect their surrounding community, represented as their core-based statistical area, within which the individual medical schools reside.